2018
DOI: 10.1111/bjir.12442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Occupational Licensing and Unions on Labour Market Earnings in Canada

Abstract: Using longitudinal data from the Canadian Survey of Labour and IncomeDynamics from 1999 to 2011, the article compares the pay and benefits of licensed and unionized workers. In a cross section of respondents and using ordinary least squares estimates, it finds a pay premium of 0.155 log points for those with an occupational licence compared to those without one; the comparable union wage premium is slightly more than half, that is 0.085 log points. Fixed-effects estimates go in the opposite direction (0.028 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…Many factors that the immigrant assimilation research literature identifies as helping immigrants are absent in non‐standard jobs. For example, presence of unions and occupational licensing were found by Zhang (2019) to improve immigrant labour market outcomes such as employment and earnings. Gomez et al (2015) found that immigrants benefit proportionally more than Canadian‐born workers from employment in a regulated occupation.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors that the immigrant assimilation research literature identifies as helping immigrants are absent in non‐standard jobs. For example, presence of unions and occupational licensing were found by Zhang (2019) to improve immigrant labour market outcomes such as employment and earnings. Gomez et al (2015) found that immigrants benefit proportionally more than Canadian‐born workers from employment in a regulated occupation.…”
Section: Discussionmentioning
confidence: 99%
“…While this quasi-natural experiment design is advantageous due to its counterfactual approach and exposition of the short-run effects of unionization at the microlevel, it has its limitations. Union elections won by a large margin may result in a more substantial wage premium (Lee and Mas 2012), possibly due to weaker bargaining power for unions that barely win certification (Zhang 2019), but cannot be examined using RDD by its definition. The RDD approach also only studies the short-run after a union election (Rios-Avila and Hirsch 2014) and is not applicable to many countries on account of heterogeneity in labor market institutions across jurisdictions (Breda 2015).…”
Section: 2: Other Methodologiesmentioning
confidence: 99%
“…Second, as mentioned previously, unions affect a number of labor market outcomes, some of which are worth summarizing here. Unions have been found to increase nonwage benefits (Freeman 1981;Zhang 2019) such as medical insurance, pension plan coverage, and paid holiday leave. Some research suggests that unions' effect on benefits is relatively larger than their effect on wages (Forth and Bryson 2019;Freeman and Medoff 1984;Knepper 2020).…”
Section: : the History Of Unions And Their General Theoretic Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, approximately 11% of Canadian workers could be identified as licensed (Zhang, 2019). Occupational regulation is highly decentralised, mainly at the provincial level.…”
Section: Box 4 Regulation Of Occupations In Other Federal Countries mentioning
confidence: 99%